ANALISIS PELAKSANAAN SISTEM AKUNTANSI PENGELUARAN KAS BELANJA MODAL DAN BELANJA PEGAWAI PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA BITUNG - Rondonuwu, Gracella Claudia; Morasa, Jenny; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Capital expenditure and personnel expenditure is one aspect that influences the government in planning the program and influential in decision making. Therefore, accounting for capital expenditures and personnel expenditures is a resource component deemed critical to meeting accountability requirements in accordance with the provisions. This study aims to determine whether the implementation of cash accounting system of capital expenditure and personnel expenditure at the Local Tax and Retribution Management Agency of Bitung City has been in accordance with applicable rules. The analytical method used is descriptive method. The result showed that the implementation of cash accounting system of capital expenditure and personnel expenditure at the Local Tax and Retribution Management Agency of Bitung City has been in accordance with the applicable Regulation of the Minister of the Interior Number 64 of 2013 regarding the Implementation of Accrual Based Government Accounting Standards. However, there are still technical errors that occur constraints in the implementation.Keywords: Cash Expenditures, Capital Expenditures, Personnel Expenditures